Effect of Different Cognitive Loads on Gait Stability in Younger and Older Adults - Mirmoezzi, Masoud; Namazizadeh, Mahdi; Sadeghi, Heydar; Mohammadi, Fariba (Physical treatments, 2019)
Purpose: As many older people fall during dual tasks, we aimed to examine the effect of different cognitive loads on learning gait stability in younger and older adults. Methods: 10 younger (Mean±SD age: 25.91±3.42 years) and 10 older adults (Mean±SD: 66.65±4.28 years) were healthy volunteers without a history of falls. They were asked to do three tasks on a treadmill with cognitive load (none, simple, and complex). The Gait-stability Ratio (GSR) was calculated in each condition. Two-way repeated-measures ANOVA was used to examine the mean differences at a significance level of 0.05. Results: The findings showed that high cognitive load behavior during preferred speed walking in the younger and older adults decreases walking speed, and subjects learn to achieve greater stability. It was determined that by applying different cognitive loads (none, simple, and complex), the GSR value in older adults was higher than younger adults (P<0.01). Conclusion: The results showed that the older adults, through different walking strategies, especially the lowering phase, provide double support while walking so that they fall less with increasing steadiness. Also, walking exercises along with complex cognitive load can help older adults to better motor control.